2017
DOI: 10.17113/ftb.55.01.17.4894
|View full text |Cite
|
Sign up to set email alerts
|

Wine Lees Polyphenols as a Novel Functional Bioactive Compound in the Protection against Oxidative Stress and Hyperlipidemia

Abstract: Wine lees are the residual precipitate formed during wine fermentation, storage, fi ltration or centrifugation (1). The (poly)phenolic compounds in lees determine the colour, intensity and organoleptic properties of wine. Through biochemical processes in lees, enzymatic activitiy induces the transformation of phenols to high value--added polyphenolic compounds with in vivo physiological activity, such as gallic acid or ellagic acid, catechin, caff eic acid, resveratrol and others (2)(3)(4)(5) SummaryThe study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 42 publications
3
33
1
Order By: Relevance
“…In an animal experiment, wine lees were shown to be a rich source of polyphenols as a basis for functional food without alcohol. They were able to compensate for an unhealthy lifestyle in the case of a high-cholesterol diet, reducing oxidative stress levels and antioxidant enzymes to control values [31]. Results of these experiments are in agreement with a previous report [32] that emphasized the seeds of red grapes as being good sources for polyphenols.…”
Section: Discussionsupporting
confidence: 91%
“…In an animal experiment, wine lees were shown to be a rich source of polyphenols as a basis for functional food without alcohol. They were able to compensate for an unhealthy lifestyle in the case of a high-cholesterol diet, reducing oxidative stress levels and antioxidant enzymes to control values [31]. Results of these experiments are in agreement with a previous report [32] that emphasized the seeds of red grapes as being good sources for polyphenols.…”
Section: Discussionsupporting
confidence: 91%
“…Tao et al (2014) [19] indicated that the content of total phenolics extracted by ultrasound ranged between 44 and 59 mg GAE/g dry matter (DM), with the final yield at the optimal conditions being 58.77 mg GAE/g DM. However, in other studies lower values were found: 30.86 and 23.16 mg GAE/g DM [28,31]. In the study carried out by Romero-Díez et al (2018), wines lees were extracted using solvents with different polarities (water, methanol, ethanol, two hydroalcoholic mixtures and acetone), and total phenolic content ranged between 26 and 254 mg GAE/g DM, with the mixture of 75:25 ( v / v ) ethanol:water showing the highest efficiency [9].…”
Section: Phenolic Compounds In Wine Leesmentioning
confidence: 84%
“…) (65,97) and hydrogen peroxide (79,98), which intensify the pathological processes resulting in the activation of inflammatory cells in the adipose tissue, endothelial dysfunction, and atherogenesis in vascular tissues (72,99). Glutathionylation, therefore, plays a complex regulatory role in obesity, metabolic syndrome-related cardiovascular diseases, and diet-induced dyslipidaemia and cholesterolaemia (83,100).…”
Section: •−mentioning
confidence: 99%